Peran public relation terhadap gairah semangat latihan pada kepengurusan divisi unit kegiatan mahasiswa seni religius - Kusuma, Muhammad Alfarizi (Maliki Interdisciplinary Journal, 2024)
This research explains how public relations can influence management performance at Religious Arts Stdent activity units UIN Malang. The population in this study were division administrators at UKM Religious Arts. . The sampling method used was interviews and public service to division administrators. The results of this research show that public relations greatly influences the management performance of Religious Arts UKM. Good public relations will produce good communication and personal relationships between fellow administrators. With public relations, you can understand the obstacles and problems that occur so that you can provide solutions to these obstacles in the form of suggestions or input.